Digital transformation of the banking sector - S. K. Yeshugova; A. K. Dorgushaova; S. K. Chinazirova; R. V. Kostenko (Новые технологии, 2019)
The introduction of digital technologies and analysis of large amounts of data makes it possible to create a fundamentally new banking products. «Digital» and technology companies enter the financial market, and large traditional banks create ecosystems, focusing on the most profitable components within the banking value chain and beyond it. Large and technologically advanced banks create their own ecosystems that open up new, unconventional sources of income. These trends determine the direction of development of the industry, and it is important for banks to take them into account in their strategies.The purpose of the article is to assess the factors influencing the innovative transformation of the banking sector by assessing the current level of digitalization of the banking sector and its industry characteristics. At the same time, modern methods of scientific knowledge, such as analysis, synthesis; induction, abstraction have been used.The article discusses the trends in the creation and implementation of innovations in the banking sector. The main directions of transforming a business model in the banking industry include the formation of their own ecosystem, the development of partnerships with other companies, provision of banking services under someone’s brand, and creation of fundamentally new lines of business based on new technologies, for example, block chain. Options for the development of traditional banks are presented.The following factors have been identified as the ones affecting the innovative transformation of the banking sector: a clear strategy and ambitious goal setting; signing partnership agreements; development of missing competencies and transformation of the corporate culture of a company.